Silver-Assisted Synthesis of Gold Nanorods: the Relation between Silver Additive and Iodide Impurities - Jessl, Sarah; Tebbe, Moritz; Guerrini, Luca; Fery, Andreas; Alvarez-Puebla, Ramon A.; Pazos-Perez, Nicolas (Small, 2018)
Seed-mediated methods employing cetyltrimethylammonium bromide (CTAB) as a surfactant, and silver salts as additives, are the most common synthetic strategies for high-yield productions of quality Au nanorods. However, the mechanism of these reactions is not yet fully understood and, importantly, significant lab-to-lab reproducibility issues still affect these protocols. In this study, the direct correlation between the hidden content of iodide impurities in CTAB reagents, which can drastically differ from different suppliers or batches, and the optimal concentration of silver required to maximize the nanorods yield is demonstrated. As a result, high-quality nanorods are obtained at different iodide contents. These results are interpreted based on the different concentrations of CTAB and cetyltrimethylammonium iodide (CTAI) complexes with Ag+ and Au+ metal ions in the growth solution, and their different binding affinity and reduction potential on distinct crystallographic planes. Notably, the exhaustive conversion of CTAI–Au+ to CTAI–Ag+ appears to be the key condition for maximizing the nanorod yield.
CRIS-Team Scopus Importer:2022-04-14
Keywords: CTAB; gold nanorods; iodide and silver relation; plasmons; seed-mediated growth